PENGARUH MODEL INKUIRI TERBIMBING TERHADAP RESPON SISWA PADA MATERI TARI KREASI KELAS XI - Yuniarti, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to determine the influence of learning inquiry model guided model against the studentâ€™s response to the creative dance of Â grade students in MAN 2 Pontianak. This research uses quantitative approach and real experiment method (Quasi Experimental). The sampel in this study are grade XI IPS 1 as experimental class and grade XI IPA 1 as control class which amounted to 40 students determined by simple way (simple random sampling). Data collection techniques used are direct observation techniques and measurement techniques. Based on the result of data analysis about the influence of learning inquiry guided model by giving one basic motion Melayu (Jepin) developed by question and answer to know how far their understing, followed by practice and conclusion from final process of learning to student response of grade XI MAN 2 Pontianak with comparing between the experimental class and the control class shows the obtained t_count of 3.431. The t_tabel value with significant level of 5 % for two sides with dk 78 then obtained equal to 1.994. Since the value of t_count>t_table, then Ho hypothesis is rejected. That is, there is the influence of learning inquiry guided model against the response of students of grade XI MAN 2 Pontianak.Â Keywords: Guided inquiry model, student response, creative dance